Mechatronic System for Maintaining the Homogeneity of Injectable Drugs in Syringe Pumps - Dumitru Adrian Draghici; Angela Repanovici (Applied Sciences)
Ensuring consistent drug concentration during intravenous (IV) administration is essential for patient safety in intensive care units (ICUs). Standard syringe pumps are prone to concentration variability due to sedimentation, molecular aggregation, and drug adsorption on plastic surfaces, especially during prolonged, low-rate infusions. We propose a novel mechatronic homogenization system integrated into syringe pumps, which combines dual-axis vibration, low-power eccentric motors, and a two-stage photonic treatment mechanism to maintain drug stability. The system is theoretically modeled and experimentally validated across multiple drug classes. Results show a significant reduction in concentration variability by over 90% compared to conventional syringe pumps, demonstrating strong potential for clinical impact. However, the study was conducted on a small class of drugs and requires a diversification of the classes of drugs that are subject to the experiment, especially in photonic treatment, where the effects on other classes of drugs administered intravenously are not fully known.